EFL Students’ Problems in Speaking: Case on Students of English Department at Dayanu Iksanuddin University - Nendy Nikita Kinski; Baharudin Baharudin (Jurnal Akademik FKIP Unidayan, 2020)
This research intended to analyze EFL students’ problems in speaking. The type of this research was qualitative. This research was conducted in Dayanu Ikhsanuddin University. In the academic year 2019, this study centered on collecting data from the speaker and fourth semester English department students as the subjects of the research. The researchers used observations and interviews when gathering data. There were three stages to the process used in data analysis, which were data reduction, data show, and conclusion drawing. The method of study was taken based on Miles and Huberman (1984)1. The outcome of this study showed that lack of confidence, anxiety, shyness, fear of making errors, inadequate vocabulary, grammatical error and lack of exposure were the problems of the EFL students in speaking. Baubau.